Alternative device concepts for future requirements of organic photovoltaic cells - Choulis, Stelios A.; Waldauf, Christoph; Denk, Patrick (My University, 2006)
The challenge to reversing the layer sequence of organic photovoltaics (OPVs) is to prepare a selective contact bottom cathode and to achieve a suitable morphology for carrier collection in the inverted structure. We report the creation of an efficient electron selective bottom contact based on a solution-processed Titania layer on top of Indium Tin Oxide. The use of o-xylene as the casting solvent creates an efficient carrier collection network with little vertical phase segregation, providing sufficient performance for both regular as well as inverted solar cells. We demonstrate inverted layer sequence OPVs with AM 1.5-calibrated power conversion efficiencies of over 3%
Keywords: Photovoltaic cells; Cathodes; Indium compounds; Morphology; Solar cells; Titanium compounds